System Dynamics Approach As A Risk Management Tool In Analyzing Pension Expenditure: The Case Of Malaysian Employees Public Pension Plan - Hasimah, Sapiri; Razman, Mat Tahar (2014)
Malaysian employees' public pension plan was studied to analyze pension expenditure due to salary risk and demographic risk. By integrating risk management and System Dynamics (SD) approach, the risk factors involved were identified, a causal loop diagram was constructed, and the SD model was developed. By using a sample of actual data, the proposed model was then validated through behavior validity test and a risk analysis was conducted. Then, risk monitoring was performed through policy evaluation in which the impact of different policy scenarios on pension expenditure was analyzed. Risk management and dynamics simulation approach in analyzing pension expenditure were shown to be useful in evaluating the impact of changes and policy decisions on risk.